2017
DOI: 10.12933/therya-17-411
|View full text |Cite
|
Sign up to set email alerts
|

Habitat use by the Antillean manatee (Trichechus manatus) during an extreme dry season in an urban lake in Tabasco, Mexico

Abstract: There are three important manatee areas in Mexico: the coasts of the State of Quintana Roo; the freshwater systems within the lower basin of the Grijalva-Usumacinta rivers, which host the largest manatee population; and the rivers of central and southern Veracruz. The Antillean manatee (Trichechus manatus manatus) is a threatened species throughout its range. In the Grijalva-Usumacinta region, two of the current threats to manatees are the effects of extremely dry periods and geographical isolation. The object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The manatees at the study site spent most of their time feeding on the bottom (BF), with SM, followed by RD. Similar behaviours have been recorded in other areas with similar environmental characteristics (Araújo & Marcondes, 2003; Castelblanco‐Martínez et al, 2009; Pablo‐Rodríguez & Olivera‐Gómez, 2012; Pablo‐Rodríguez et al, 2016; Ramírez‐Jiménez et al, 2017). The SM is associated with exploring the environment in search of food (Bailey et al, 1996).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The manatees at the study site spent most of their time feeding on the bottom (BF), with SM, followed by RD. Similar behaviours have been recorded in other areas with similar environmental characteristics (Araújo & Marcondes, 2003; Castelblanco‐Martínez et al, 2009; Pablo‐Rodríguez & Olivera‐Gómez, 2012; Pablo‐Rodríguez et al, 2016; Ramírez‐Jiménez et al, 2017). The SM is associated with exploring the environment in search of food (Bailey et al, 1996).…”
Section: Discussionsupporting
confidence: 78%
“…The behavioural ecology of free‐ranging T. manatus was first studied in the 1970s in Florida, focusing on the Florida manatee subspecies, T. m. latirostris (Hartman, 1979). Behavioural research of Antillean subspecies ( T. m. manatus ) has focused on populations in the Caribbean and Central America (Castelblanco‐Martínez et al, 2013; Alvarez‐Alemán et al, 2017; Ramírez‐Jiménez et al, 2017), and there are a few behavioural studies in the wild in Brazil (Paludo & Langguth, 2002; Alves, 2003; Silva et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant category is 'Conservation' (16.6%), which includes quantitative or qualitative descriptions of threats to manatee viability/health such as boat collisions (e.g., Borges et al, 2007), poaching (e.g., Jiménez-Pérez, 2002), contaminants (e.g., Anzolin et al, 2012; Romero-Calderón et 1980-1982 1983-1987 1988-1992 1993-1997 1998-2002 2003-2007 2008 1980-1982 1983-1987 1988-1992 1993-1997 1998-2002 2003-2007 2008 (e.g., Vanoye, 2002;Silva et al, 2009;Takeuchi et al, 2016). In the topic behavior (10.3%), papers approaching aspects on manatee communication (e.g., Alicca et al, 1997;Sousa-Lima et al, 2008;Umeed et al, 2018;Merchan et al, 2019;Ramos et al, 2020), learning and welfare (e.g., Hénaut et al, 2020), husbandry (Lima et al, 2005), circadian rhythm (Holguin-Medina et al, 2015), habitat preferences (e.g., Ramírez-Jiménez et al, 2017), and movements and migrations (e.g., Castelblanco-Martínez et al, 2013) were found.…”
Section: Resultsmentioning
confidence: 99%
“…Not surprisingly, the majority of the work has occurred in Mexico, because that is where the technique was first described and had the best results in the initial study (Gonzalez-Socoloske et al, 2009). However, it was surprising to see the number of unique locations (at least seven, including Catazajá wetlands in Chiapas, Alvarado Lagoon System in Veracruz, Laguna de las llusiones, Pantanos de Centla, and San Pedro River in Tabasco, Laguna de Terminos in Campeche, and Rio Hondo in Quintana Roo) and independent research groups (at least seven) within Mexico that are using the methodology (Rodas-Trejo et al, 2008;Gonzalez-Socoloske et al, 2009;Daniel-Rentería et al, 2012;Gonzalez-Socoloske & Olivera-Gomez, 2012;Acevedo-Olvera et al, 2015;Puc-Carrasco et al, 2016;Puc-Carrasco et al, 2017;Ramírez-Jiménez et al, 2017;Serrano et al, 2017;Ladrón de Guevara-Porras et al, 2019;Corona-Figueroa et al, 2021, 2022. The 15 countries with confirmed use of side-scan sonar are likely an underrepresentation of the overall number because there are some localities where it has been used, but they are yet to publish their results in any format that we were able to assess.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many studies have indicated that in seasonally flooding systems (e.g. Alvarado Lagoon System, Usumacinta-Grijalva Basin, Orinoco Basin, Sanaga River Basin, Amazon River Basin), the dry season provides the best opportunities to use the technology due to the concentration of the manatees and the shallow water (Arévalo-González et al, 2014;Ramírez-Jiménez et al, 2017).…”
Section: Types Of Habitats Where Side-scan Sonar Has Been Effectivementioning
confidence: 99%